Alkaline Polymer Membrane‐Based Ultrathin, Flexible, and High‐Performance Solid‐State Zn‐Air Battery. Issue 14 (14th February 2019) - Wang, Wang; Tang, Meihua; Zheng, Zhenying; Chen, Shengli
Abstract: The increasing demand for portable and wearable electronics requires lightweight, thin, and highly flexible power sources, for example, flexible zinc‐air batteries (ZABs). The so‐far reported flexible ZAB devices mostly remain bulky, with a design consisting of two relatively thick substrates (e.g., carbon cloths and/or metal foams) and a gel electrolyte‐coated separator in between. Herein, an ultrathin (≈0.2 mm) solid‐state ZAB with high flexibility and performance is introduced by directly forming self‐standing active layers on each surface of an alkaline polymer membrane through an ink‐casting/hot‐pressing approach. A Fe/N‐doped 3D carbon with hierarchic pores and an interconnected network structure is used as cathode electrocatalyst, so that the backing gas‐diffusion layer (e.g., carbon cloth) can be abandoned. What is further, a microstructure‐modulating method to significantly increase the FeN4 active sites for oxygen reduction reaction is developed, thus significantly boosting the performance of the ZAB. The assembled solid‐state ZAB manifests remarkable peak power density of 250 mW cm −3 and high capacity of 150.4 mAh cm −3 at 8.3 mA cm −3, as well as excellent flexibility. The new design should provide valuable opportunity to the portable and wearable electronics. Abstract : An ultrathin solid‐state Zn‐air battery ( ≈0.2 mm in thickness) with high flexibility and performance is constructed by directly forming self‐standing active layers on each surface of an alkaline polymer membrane through an ink‐casting approach, and by using a micropore‐digging method to significantly increase the FeN4 active sites in cathode oxygen reduction catalyst.